ChemInform Abstract: Diospentenols A (I) and B (II), Two New Cyclopentapyrans Isolated from Abandoned Mine Bacterium Streptomyces sp. KMA‐001. Issue 18 (17th April 2014) - Park, Jin‐Soo; Cha, Jin Wook; Kim, Seong‐Hwan; Oh, Dong‐Chan; Kwon, Hak Cheol
Abstract: Both compounds (I) and (II) are obtained as racemic mixtures and their absolute configurations are not determined.